PREVENTION OF OBESITY IN CHILDREN AND ADOLESCENTS COMBINED WITH PHYSICAL EXERCISES AND HEALTHY EATING (CIPEEX, 2022)
OBESITY IS CONSIDERED A CHRONIC DISEASE AND AN EPIDEMIC OF THE 21ST CENTURY AND IS DEFINED AS THE ABNORMAL ACCUMULATION OF FAT THAT POSES A HEALTH RISK. GLOBAL TRENDS TOWARDS A SEDENTARY LIFESTYLE AND NUTRIENT-POOR DIET HAVE LED TO AN INCREASE IN THESE DISEASES AMONG CHILDREN AND ADOLESCENTS. THEREFORE, THIS MINI-REVIEW AIMS TO UNDERSTAND WHETHER CHILDREN AND ADOLESCENTS WITH A HEALTHIER LIFESTYLE, BASED ON PHYSICAL EXERCISE AND HEALTHY EATING, ARE LESS LIKELY TO DEVELOP OBESITY. FOR THIS, ARTICLES FROM GOOGLE SCHOLAR AND SCIELO WERE USED AND, AS INCLUSION CRITERIA, THE PORTUGUESE OR ENGLISH LANGUAGES, PUBLICATION DATE OF THE LAST 5 YEARS, ARTICLES AVAILABLE FREE OF CHARGE AND COMPLETE AND WHICH WERE CLINICAL TRIALS. THE RESULTS ACHIEVED BY THEM DEMONSTRATED THAT THERE IS INDEED A RELATIONSHIP BETWEEN THESE TWO FACTORS AND THE REDUCTION OF BODY MASS. THUS, PREVENTIVE PRACTICES FOR OVERWEIGHT AND OBESITY IN CHILDREN AND ADOLESCENTS RELATED TO AEROBIC ACTIVITIES AND HEALTHY FOODS ARE IMPORTANT.
Keywords: obesity; young people; healthy food; physical exercise